Axial load tests and analysis for open-ended steel tubular piles driven into weathered rock. - Han, Yi. (University of Ottawa (Canada), 1999)
The bearing capacity of tubular, open-ended steel piles driving into weathered rock was investigated using static load tests, finite element analysis and dynamic load tests. Dynamic load tests were carried out by using the Case Method and the CAPWAP Method which were used to determine the bearing capacity of piles. The effects of final set, pile burial length, setup and other factors on the pile bearing capacity were evaluated. In the static load tests, two piles with 0.813 m diameter and one pile with a diameter of 1.0 m were tested. The finite element analysis was performed to back calculate the load-displacement response of piles. A hyperbolic model for soils and an elastic-plastic model for rocks were used in the study. A parametric study was also carried out. The issues, such as the effects of pile installation and soil plug, were discussed.
Keywords: Engineering, Civil.